Wavelet-Based Frequency Response Function: Comparative Study of Input Excitation - K. Dziedziech; W. J. Staszewski; T. Uhl (Shock and Vibration)
Time-variant systems can be found in many areas of engineering. It is widely accepted that the classical Fourier-based methods are not suitable for the analysis and identification of such systems. The time-variant frequency response function—based on the continuous wavelet transform—is used in this paper for the analysis of time-variant systems. The focus is on the comparative study of various broadband input excitations. The performance of the method is tested using simulated data from a simple MDOF system and experimental data from a frame-like structure.